Makna Otonomi Ekonomi Perempuan dalam Lagu Miss Independent: Analisis Semiotika Roland Barthes - Fellycia Muaya; Diah Ayu Candraningrum (Koneksi, 2026)
This study examines the representation of perceptions of women’s economic autonomy in Ne-Yo’s "Miss Independent" (2008) using Roland Barthes’ semiotic approach. The lyrics serve as the subject, while the focus is on understanding how young women internalize messages of financial independence, decision- making freedom, and self-reliance. Analysis is conducted across three semiotic levels: denotation, connotation, and myth, to explore how the song constructs the image of an independent woman. Findings indicate that the lyrics reinforce liberal feminist values by emphasizing autonomy, equality, and empowerment, while also reflecting the social realities and aspirations of. The study demonstrates that popular music functions as a cultural medium that can shape perceptions, inspire agency, and foster critical media literacy. By linking lyrical representation with the lived experiences of young women, this research highlights the role of music in promoting gender equality and empowering to embrace independence both socially and economically. The study contributes to cultural communication scholarship and provides insight for creating more inclusive and empowering cultural works.     Penelitian ini menelaah representasi persepsi terhadap otonomi ekonomi perempuan melalui lirik lagu Ne-Yo, "Miss Independent" (2008) menggunakan pendekatan semiotika Roland Barthes. Subjek penelitian adalah lirik lagu, sedangkan objeknya adalah kemandirian ekonomi perempuan, termasuk kemampuan mengelola keuangan, membuat keputusan, dan menegaskan identitas diri. Analisis dilakukan pada tiga tingkatan makna: denotasi, konotasi, dan mitos, untuk memahami bagaimana lagu membangun citra perempuan mandiri. Temuan menunjukkan bahwa lirik lagu menguatkan nilai-nilai feminisme liberal dengan menekankan otonomi, kesetaraan, dan pemberdayaan, sekaligus mencerminkan realitas sosial dan aspirasi. Musik populer berfungsi sebagai medium budaya yang membentuk persepsi, mendorong kemandirian, dan meningkatkan literasi media kritis. Dengan menghubungkan representasi lirik dan pengalaman nyata perempuan muda, penelitian ini menyoroti peran musik dalam mempromosikan kesetaraan gender dan memberdayakan perempuan untuk mandiri secara sosial dan ekonomi. Studi ini diharapkan memperkaya kajian komunikasi budaya serta memberikan inspirasi bagi penciptaan karya yang lebih inklusif dan memberdayakan.